Inborn Errors of the Immune System Associated With Atopy - Nelson, Ryan W.; Geha, Raif S.; McDonald, Douglas R. (Frontiers in Immunology, 2022)
Atopic disorders, including atopic dermatitis, food and environmental allergies, and asthma are increasingly prevalent diseases. Atopic disorders are often associated with eosinophilia, driven by T helper type 2 (Th2) immune responses, and triggered by disrupted barrier function leading to abnormal immune priming in a susceptible host. Immune deficiencies, in contrast, occur with a significantly lower incidence, but are associated with significantly greater morbidity and mortality. A subset of atopic disorders with eosinophilia and/or elevated IgE are associated with monogenic inborn errors of immunity (IEI). In this review we will discuss current knowledge of IEI that are associated with atopy and the lessons these immunologic disorders provide regarding the fundamental mechanisms that regulate type 2 immunity in humans. We will also discuss further mechanistic insights provided by animal models.